Statistical optimization and electrochemical analysis of gambir extract as a corrosion inhibitor for SS-316 in hydrochloric acid - Suprapto Suprapto; Handi Ardiansyah; Djarot Sugiarso; Kartika A. Madurani; Yosephine S.W. Manuhara; Syamsuardi Syamsuardi (Case Studies in Chemical and Environmental Engineering)
The anti-corrosive properties of Gambir extract on SS-316 stainless steel were studied. It was found that the addition of Gambir extract in the HCl solution decreased the SS-316 average corrosion current density (I_corr) compared to the blank solution. The response surface methodology plot showed that I_corr increased with increasing HCl concentration and contact time, but decreased with higher concentrations of Gambir extract, indicating its effectiveness in inhibiting corrosion even under harsher conditions. Surface characterization confirmed the formation of this protective layer, while FTIR analysis identified the main functional groups involved in the metal-inhibitor interaction.